Analysis and synthesis of spatial quality in 1/6 gravity of earth- with respect to the moon- with special attention to human physiology and psychological essentials - Halder, Emil Theodore (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2013.